A study on channel and delay-based scheduling algorithms for live video streaming in the fifth generation long term evolution-advanced - Abdul Latiff, Liza; Mohd Ramli, Huda Adibah; Asnawi, Ani Liza; Abdul Wahab, Nur Haliza (IIUM Press, 2022)
This paper will investigate the performance of a number of channel and delay-based scheduling algorithms for an efficient QoS (Quality of Service) provision with more live video streaming users over the Fifth Generation Long-Term Evolution-Advanced (5G LTE-A) network. These algorithms were developed for use in the legacy wireless networks and minor changes were made to enable these algorithms to perform packet scheduling in the downlink 5G LTE-A. The efficacies of the EXP and M-LWDF algorithms in maximizing the number of live video streaming users at the desired transmission reliability, minimizing the average network delay, and maximizing network throughput are shown via simulations. As the M-LWDF having a simpler mathematical equation as compared to the EXP, it is more favoured for implementation in the complex downlink 5G LTE-A